2019
DOI: 10.2147/ppa.s234449
|View full text |Cite
|
Sign up to set email alerts
|

<p>Adult Perceptions of Different Orthodontic Appliances</p>

Abstract: Introduction: Pursuing an esthetically-pleasing orthodontic outcome, orthodontic patients must consider and choose from the different available options of orthodontic appliance. Practitioners need to be better informed of their customers’ preferences to make better practice management decisions and satisfy their patients’ needs.PurposeTo explore adult laypeople’s perceptions of the attractiveness, acceptability, preference and economic value of different orthodontic appliances when they consider these applianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 16 publications
0
39
0
2
Order By: Relevance
“…Both studies found that adult patients are willing to pay for more esthetic orthodontic appliances for their own but not for their children. 21 , 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies found that adult patients are willing to pay for more esthetic orthodontic appliances for their own but not for their children. 21 , 25 …”
Section: Discussionmentioning
confidence: 99%
“…Both studies found that adult patients are willing to pay for more esthetic orthodontic appliances for their own but not for their children. 21,25 This is a cross-sectional survey, thus, there might be a limitation of information bias. The patients might not be fully aware of the type of surgeries, medications, or customized appliances used to accelerate orthodontic tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] However, lay people's perception of orthodontic appliances revealed differences that may vary with age and social or cultural values. [8][9][10][11][12][13] Adults from the USA and Brazil were found to give high esthetic value to inconspicuous appliances such as clear aligners, lingual brackets, and tooth-colored brackets. 8,9 A study found Iranian adults to also prefer clear aligners but to extremely disapprove of lingual brackets.…”
Section: Introductionmentioning
confidence: 99%
“…11 Adults in Saudi Arabia also echoed American and Brazilian adults in their high preference for inconspicuous orthodontic appliances like clear aligners and lingual brackets. 13 To investigate the esthetic value of orthodontic appliances for youth consumers, some studies asked adults about their preference for their kids. 9,12,13 Only two studies from the United States and Brazil directly addressed youth orthodontic appliance preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation